Village and (dis)trust in the political institution of the society - Šarović, Rade; Ceranic, Goran (Sociološki pregled, 2022)
Тhe subject of this paper is the (dis)trust of peasants towards the social order and political institutions of the Montenegrin system. This relationship is most often reflected in the fact that peasants are more subordinate to the global society, the state and the ruling regime than all other strata in one system. In small societies such as Montenegro, their influence as a political factor and an active participant in the creation of political life is minor. This exclusion is primarily the result of the small number of people remaining to live and work in the village today, and of their demographic characteristics. The involvement in public action is reduced to the execution of orders, payment of taxes, and voting in elections to support or not support those in power. Hence the story of peasants‘ (dis) trust in the institutional system they live in.
Keywords: village; Montenegro; trust; society; politics; institutions